Bile Cast Nephropathy Secondary to Hemophagocytic Lymphohistiocytosis With Liver Failure - Chango Azanza, Juan Jose (Cureus, 2020)
Acute kidney injury (AKI) is a common complication seen in patients with hemophagocytic lymphohistiocytosis (HLH). More than half of patients with HLH require renal replacement therapy (RRT). There are four main causes of kidney dysfunction in HLH, which include acute tubular necrosis (ATN), hypoperfusion, tumor lysis syndrome (TLS), and HLH-related glomerulopathies. Bile cast nephropathy (BCN) is a known cause of kidney injury in patients with liver failure and hyperbilirubinemia. We present the case of a 58-year-old man who presented to the hospital with painless jaundice, choluria, acholia, and generalized malaise and was found to have hyperbilirubinemia and kidney injury in the setting of HLH, who underwent a renal biopsy showing bile salt casts with degenerating tubular lining cells consistent with BCN. This case highlights the importance of considering BCN as a cause of kidney injury when a patient with HLH presents with liver failure and elevated bilirubin levels.